2006
DOI: 10.1111/j.1748-5827.2006.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant mutation causing the dorsal ridge predisposes for dermoid sinus in Rhodesian ridgeback dogs

Abstract: Rhodesian ridgeback dogs that carry the ridge trait are predisposed to dermoid sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 4 publications
1
21
0
1
Order By: Relevance
“…Hillbertz et al identified a 133 Kb duplication on chromosome 18 that associated perfectly with the presence of the ridge of hair growing in the opposite direction along the spine of the Rhodesian ridgeback (62). In addition, Drögmüller and colleagues found a frameshift variant in the FOXI3 gene that segregated with the hairless phenotype, also called ectodermal dysplasia (CED), in the Chinese crested breed (37).…”
Section: Morphology and Breedsmentioning
confidence: 99%
“…Hillbertz et al identified a 133 Kb duplication on chromosome 18 that associated perfectly with the presence of the ridge of hair growing in the opposite direction along the spine of the Rhodesian ridgeback (62). In addition, Drögmüller and colleagues found a frameshift variant in the FOXI3 gene that segregated with the hairless phenotype, also called ectodermal dysplasia (CED), in the Chinese crested breed (37).…”
Section: Morphology and Breedsmentioning
confidence: 99%
“…The breed-defining characteristic is a dorsal ridge, caused by a lateral instead of caudal orientation of the hair in this region (10). The RR reflects a mixture of several European dog breeds and the local ridged Hottentot Khoi dog and was initially bred for lion hunting (10,11). The presence of multiple affected dogs with a distinct phenotype in many litters proposed an inherited condition, which warranted us to embark a comprehensive study to describe the clinical features and find the genetic cause.…”
mentioning
confidence: 99%
“…Dermoid sinus is considered a hereditary neural tube abnormality in Rhodesian Ridgebacks [39,40]. Their characteristic cutaneous ridge in this breed is an autosomal dominant mutation of fibroblast growth factor genes that predispose the animals to dermoid sinus [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Their characteristic cutaneous ridge in this breed is an autosomal dominant mutation of fibroblast growth factor genes that predispose the animals to dermoid sinus [39,40]. This developmental abnormality has been reported in several other breeds, including the American Cocker Spaniel, English Cocker Spaniel, English Springer Spaniel, Boxer, Chow-Chow, Golden Retriever, Shih Tzu, Siberian Husky, Yorkshire Terrier, German Shepherd, Rottweiler, Boerboel, Great Pyrenees, Swedish Vallhund, Chinese Crested, Victorian Bulldog, and occasionally in domestic cats [6-8,11-14,16,17,41-46].…”
Section: Discussionmentioning
confidence: 99%